Urinoma: A Rare Complication of Abdominal Aortic Aneurysm Surgery - Koon-Sung Cheng; Hashim Hashim; Janice Tsui; Caroline Osborne; Nickolas Law (The Scientific World Journal)
Urinoma or para-renal pseudocyst generally occurs as a result of trauma to the pelvi-ureteric system. It consists of an encapsulated collection of extravasated urine and is usually located in the peri-renal space or more uncommonly in the peritoneal, pleural or mediastinal cavities. There is only one previously reported case of urinoma secondary to abdominal aortic aneurysm (AAA) surgery. We report a case of symptomatic urinoma after infra-renal AAA repair and discuss the etiology, diagnosis and treatment of this unusual condition.